A racism-critical look at language-related discrimination in access to welfare state benefits and the labor market - Holzinger, Clara; Draxl, Anna-Katharina (Momentum Quarterly, 2024)
From a racism-critical perspective, this article addresses the question of how social inequalities are (re)produced through language-related practices. Using results from three empirical research projects, we show how linguistic and racist discrimination are intertwined when it comes to accessing welfare state benefits and the labor market. Our data demonstrates how exclusion processes occur in both fields through linguistic practices. Despite the empirical entanglement of linguicism and racism, we also argue in favor of paying attention to differences between these two types of discrimination in order not to lose sight of linguistic discrimination beyond racism on the one hand and to recognize the masking of racism through linguistic discrimination on the other.
Keywords: access to welfare state services; labour market discrimination; migration research; linguicism; racism